Hegemony of Political Parties and Regional Political Oligarchy - Roso Prajoko; Ari Pradhanawati; Fitriyah Fitriyah; Nur Hidayat Sardini (UIN Sunan Gunung Djati, 2024)
This study aims to delve into the prevalence of single candidates participating in regional elections across various regions following the Constitutional Court Decision Number 100/PUU-XIII/2015. It explores how political party elites and oligarchs strategically maneuver to either maintain or acquire power. Specifically focusing on Boyolali Regency, this research employs a qualitative descriptive approach to uncover the underlying causes behind the emergence of a single candidate. The findings reveal the significant influence of hegemonic forces wielded by major political parties over smaller ones, orchestrated by oligarchs. Importantly, the study highlights that this hegemonic dominance is not driven by factors such as religious majority affiliations with political parties but rather emerges as a purely oligarchic endeavor aimed at controlling both the nomination process and victory outcomes of single candidates.